Retorno ao presencial: uma análise comportamental dos discentes do Polo Universitário de Oeiras do Pará em relação às orientações de biossegurança da UFPA - COELHO, Izabel Nogueira (2024)
The return to face-to-face teaching imposed changes on the dynamics within universities, establishing new rules for living together and using public space. The Federal University of Pará (UFPA) through the Working Group (GT) on the Coronavirus prepared biosafety guidelines for the use of institutional spaces, with the aim of preventing or reducing as much as possible contagion in the academic field. In this sense, in times of a pandemic, declared by the World Health Organization (WHO), we want to investigate and discuss whether the students of the Polo Universitário de Oeiras do Pará – Campus/Cametá, would be following the biosafety guidelines. The information that guided the work was carried out through internet searches through the application called Google forms, and the data were analyzed taking into account qualitative criteria for a better understanding of how students behaved in this epidemiological scenario during the class period.